2000
DOI: 10.1111/j.1945-5100.2000.tb01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of feldspathic and metallic melts by shock in enstatite chondrite Reckling Peak A80259

Abstract: Abstract-The enstatite chondrite Reckling Peak (RKP) A80259 contains feldspathic glass, kamacite, troilite, and unusual sets of parallel fine-grained enstatite prisms that formed by rapid cooling of shock melts. Metallic Fe,Ni and troilite occur as spherical inclusions in feldspathic glass, reflecting the immiscible Fe-Ni-S and feldspathic melts generated during the impact. The Fe-Ni-S and feldspathic liquids were injected into fractures in coarse-grained enstatite and cooled rapidly, resulting in thin (110 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 29 publications
6
19
0
Order By: Relevance
“…The initial (nanosecond-scale) peak pressure in the shock front and the resulting shock temperature can have grain-to-grain variations of an order of magnitude (Sharp and DeCarli, 2006). Because many EH and EL chondrites have been altered by impacts (e.g., Kimura and Lin, 1999;Burbine et al, 2000;Fagan et al, 2000;Patzer et al, 2004;Keil, 2007) and because impact processes can produce changes in bulk composition (e.g., ) and mineralogy (e.g., ) on a scale of $10 mm (e.g., , the standard taxonomic parameters may yield different results for different samples. Caution must therefore be taken in weighting these parameters.…”
Section: Impact-melting In the Eh6 Chondritesmentioning
confidence: 97%
See 1 more Smart Citation
“…The initial (nanosecond-scale) peak pressure in the shock front and the resulting shock temperature can have grain-to-grain variations of an order of magnitude (Sharp and DeCarli, 2006). Because many EH and EL chondrites have been altered by impacts (e.g., Kimura and Lin, 1999;Burbine et al, 2000;Fagan et al, 2000;Patzer et al, 2004;Keil, 2007) and because impact processes can produce changes in bulk composition (e.g., ) and mineralogy (e.g., ) on a scale of $10 mm (e.g., , the standard taxonomic parameters may yield different results for different samples. Caution must therefore be taken in weighting these parameters.…”
Section: Impact-melting In the Eh6 Chondritesmentioning
confidence: 97%
“…Many EH chondrites have been described as impactmelt breccias or impact-melt rocks (e.g., Rubin, 1997a;Lin and Kimura, 1998;Kimura and Lin, 1999;Burbine et al, 2000;Fagan et al, 2000;Keil, 2007). The heat generated by the associated impacts could potentially cause thermal metamorphism in these materials, a process involving recrystallization, mineral equilibration, and partial loss of highly volatile elements.…”
Section: Introductionmentioning
confidence: 97%
“…of production of the schreibersite microspherules together with their host sulfides. Shock-induced melt inclusions of metallic Fe-Ni and troilite were reported in RPKA80259 (Fagan et al, 2000), but they are usually enclosed in silicates and not in sulfides. Many immiscible sulfide melt inclusions have been found in oldhamite from the Pefia Blanca Springsaubrite.…”
Section: Nebular Processesmentioning
confidence: 99%
“…The major and minor elemental (Na, K, Mg, Al, Cr, Si, P, K, Ca, Ti, Mn, and Fe) compositions of the melt inclusions and their hosts were measured on a Cameca SX-50 electron microprobe at Virginia Tech (Table 1). Previous work by Fagan et al (2000) on glass analyses showed that using an accelerating voltage of 15 kV, a current of 2 nA and a defocused beam (5 to 10 µm) minimizes loss of Na, and so these instrumental conditions were employed in this study. In addition, Na was always analyzed first to minimize its loss during exposure to the beam.…”
Section: Sample Preparation Experimental and Analytical Methodsmentioning
confidence: 99%